Using antibody catalysis to study the outcome of multiple evolutionary trials of a chemical task - Karlstrom, Amelie (The National Academy of Sciences, 2000)
Catalytic aldolase antibodies generated by immunization with two different, but structurally related, β-diketone haptens were cloned and sequenced to study similarities and differences between independently evolved catalysts. Kinetic and sequence analysis coupled with mutagenesis, structural, and modeling studies reveal that the defining event in the evolution of these catalysts was a somatic mutation that placed a lysine residue in a deep, yet otherwise unrefined, hydrophobic pocket. We suggest that covalent chemistries may be as readily selected from the immune repertoire as the traditional noncovalent interactions that have formed the basis of immunochemistry until this time. Further, we believe that these experiments recapitulate the defining events in the evolution of nature's enzymes, particularly as they relate to chemical mechanism, catalytic promiscuity, and gene duplication.